Le grand portail de Cluny III : les interférences de la tradition tardo-antique, romaine et islamique sur un monument atypique - Christe, Yves (Hortus Artium Medievalium, 2014)
Abstract On the basis of the reconstruction of K. J. Conant, restitution which is confirmed by a recent critical examination, we should wonder about the atypical disposition of the Majestas Domini, a triumphal Ascension, which occupies the tympanum and the lintel of the great portal of Cluny III. The model of this theophany is italian, inspired by the absidal iconography at the end of the XIth century, in Rome and around the Monte Cassino: Sant Angelo in Formis and Santa Restituta of Naples. This explains the centric position of the beasts of Apocalypse and the Elders without their crowns. In the same time, the architectural structure of the portal send back to the lateral entrance of the great Mosque of Cordoba and most of all to the absidal arch of the oratory of the mihrab.